HUBUNGAN GAYA KEPEMIMPINAN INSTRUKTUR KLINIK TERHADAP EFEKTIFITAS PEMBELAJARAN PRAKTIK KLINIK KEBIDANAN BERDASARKAN PERSEPSI MAHASISWA D-III KEBIDANAN UNIVERSITAS BATAM TAHUN 2017 - Sani, Rumondang Mutiara; Susanti, Susanti (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2017)
According to the Decree of National Education Minister No. 232/U/2000 in Terms of Reference and Guidelines of Curriculum Compilation on Higher Education and Academic Scoring System, it reveals that the residency requirement to qualify for a diploma is 40% of theory classes and 60%. This research aims to investigate the correlation of a clinic instructor leadership and the effectiveness of the midwifery clinic practice courseÂ  according to the perception of the D III Midwifery students of the Batam University in 2017. The research method employs observational study with cross-sectional design. The research was conducted in June â€“ July 2017 by involving 38 respondents as the total sample population. The primary data collecting technique employs questionnaire. The data analyzing technique employs the frequency distribution tables. The research result demonstrates that according to the student perception, the democratic-styled leadership that runs effectively is admitted by 29 respondents (76.3%);the authoritarian-styled leadership that runs effectively is admitted by 5 respondents (13.2%), and the other more flexible-styled leadership that runs effectively is admitted by 4 respondents (10.5%). the chi-square test reveals p value = 0.000 (<0.05). In conclusion, there is significant correlation between a clinic instructor leadership and the effectiveness of the midwifery clinic practice course according to the perception of the D III Midwifery students of the Batam University in 2017.Â